“Pure Fat Flap”—Perforator-based Adiposal Layer Only Flap for Lateral Ankle Reconstruction - Seok Joon Lee; Jeongmok Cho; Changsik Pak; Hyunsuk Suh; Joon Pio Hong (Archives of Plastic Surgery)
Lateral ankle soft tissue defects pose challenges, especially in cases due to chronic pressure from cross-legged sitting, which usually present with a large dead space, small skin opening that often accompanies an open joint. Traditional reconstruction methods using fasciocutaneous flaps may result in donor site morbidity such as delayed wound healing or nerve injury. In this article, we present a case of diabetes-related lateral ankle defect successfully treated using adiposal layer only flap, also known as pure fat flap. The anatomy and the surgical technique of adiposal layer only flap were reviewed. These flaps preserve the subdermal plexus and deep fascia while obliterating dead space and providing a gliding surface for proper ankle movement. A perforator-based adiposal layer only flap was elevated from the peroneal artery and used to cover the defect. Flap perfusion was confirmed using indocyanine green video angiography and color duplex ultrasound. Patient had a successful recovery with minimal donor site morbidity. The technique expands the reconstructive microsurgeon's options for complex ankle coverage, ensuring optimal wound healing and functional outcomes.